2009
DOI: 10.1089/ten.tea.2008.0169
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Early Embryonic Cardiac Tissue Increases Cardiomyocyte Proliferation by Cyclic Mechanical Stretch via p38-MAP Kinase Phosphorylation

Abstract: Cardiomyocyte (CM) transplantation is one therapeutic option for cardiac repair. Studies suggest that fetal CMs display the best cell type for cardiac repair, which can finitely proliferate, integrate with injured host myocardium, and restore cardiac function. We have recently developed an engineered early embryonic cardiac tissue (EEECT) using embryonic cardiac cells and have shown that EEECT contractile properties and cellular proliferative response to cyclic mechanical stretch stimulation mimic developing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 52 publications
(33 reference statements)
3
45
0
Order By: Relevance
“…Previous studies have shown that cyclic mechanical stretch improves cardiomyocyte orientation 49 and proliferation, 50 and promotes hypertrophy. 51 Further, active forces between 0.05 and 2 mN have been previously reported after mechanical stimulation 52 ; Cx43 mRNA expression is increased threefold 49,53 and phosphorylated Akt expression increased 40% in mechanically stretched constructs when compared with static conditions.…”
Section: Fig 8 Growth Signaling Proteins (A)mentioning
confidence: 94%
“…Previous studies have shown that cyclic mechanical stretch improves cardiomyocyte orientation 49 and proliferation, 50 and promotes hypertrophy. 51 Further, active forces between 0.05 and 2 mN have been previously reported after mechanical stimulation 52 ; Cx43 mRNA expression is increased threefold 49,53 and phosphorylated Akt expression increased 40% in mechanically stretched constructs when compared with static conditions.…”
Section: Fig 8 Growth Signaling Proteins (A)mentioning
confidence: 94%
“…36 Using a similar system based on collagen and Matrigel, Clause et al generated engineered early embryonic cardiac tissue using embryonic cardiac cells from chicken. 37 They reported a 1.6-fold increase in active stress at L max following cyclic mechanical stretch stimulation for 48 h and concluded that contractile properties and cellular proliferative response to stretch mimic developing fetal myocardium.…”
Section: Kensah Et Almentioning
confidence: 98%
“…10-day cyclic mechanical stretch increased cardiomyocyte proliferation via p38 MAPK phosphorylation. 39 Shear stress induced proliferation of rat mesenchymal stem cells through pim-1 via ERK and p38 MAPK. 40 Oscillatory flow induces human osteoblast-like MG63 cell proliferation through activation of b3 and b1 integrins leading to the modulation of downstream ERK and Akt pathways.…”
Section: Stretch Increases Proliferation Without Differentiation In Dmentioning
confidence: 99%